First-cut design of an all-superconducting 100-T direct current magnet - Iwasa, Yukikazu (AIP Publishing LLC, 2013)
A 100-T magnetic field has heretofore been available only in pulse mode. This first-cut design demonstrates that a 100-T DC magnet (100 T) is possible. We base our design on: Gadolinium-based coated superconductor; a nested-coil formation, each a stack of double-pancake coils with the no-insulation technique; a band of high-strength steel over each coil; and a 12-T radial-field limit. The 100 T, a 20 mm cold bore, 6-m diameter, 17-m height, with a total of 12 500-km long superconductor, stores an energy of 122 GJ at its 4.2-K operating current of 2400 A. It requires a 4.2-K cooling power of 300 W.